Anti-inflammatory Diet for Interstitial Cystitis (AID-IC): Study Protocol for a Randomized Controlled Cross-Over Trial. (7th June 2021) - Gordon, Barbara; !Blanton, Cynthia
Abstract: Objectives: IC/BPS is characterized by pelvic pain, pressure, or discomfort in the bladder and pelvic area coupled with urinary frequency and urgency. The cause is unknown. Dietary intake appears to exacerbate IC/BPS symptoms for many patients; however, the association is not well understood. The potential role of saturated fat and other inflammatory dietary components in provoking IC/BPS symptoms will be explored. Animal studies associate high dietary intake of saturated fats with activation of toll-like receptor (TLR4) cell signaling and pro-inflammatory responses. Saturated free fatty acids were linked to changes in the bladder on a cellular level. The goal of the AID-IC study is to investigate the efficacy of an anti-inflammatory diet (limits lipid intake and increases antioxidant intake) on symptom severity. Methods: In a 22-week, crossover study, women with IC/BPS will be randomized into two groups. Group one will receive 10 weeks of a therapeutic anti-inflammatory diet that eliminates foods commonly bothersome for those with this condition; 5 days/week prepared, home-delivered meals were provided. Group 2 will receive counseling from a dietitian on standard IC/BPS dietary recommendations (control diet). After a two-week washout period, dietary interventions for the two groups will be switched. Primary outcomes include changes in inflammatory biomarkers (TNF-alpha and IL-1) and scores on three validated symptom severity surveys. Results: We hypothesize that an anti-inflammatory diet that excludes foods commonly bothersome for individuals with IC/BPS will help manage symptomology for these patients. Furthermore, we hypothesize that the severity of symptoms will be mediated by the reduction of pro-inflammatory responses associated with the influence of a diet low in saturated fats and high in anti-inflammatory dietary components. Conclusions: The feasibility of managing IC/BPS symptoms by influencing inflammatory activity via restricting lipid intake and increasing antioxidant-rich foods has not previously been investigated. The findings may offer preliminary data on a cost-effective, noninvasive therapy. Funding Sources: Mountain West Clinical & Translational Research Infrastructure Network (National Institute of General Medical Sciences, NIH).